2023
DOI: 10.1177/00033197231161902
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Serum Uric Acid to Albumin Ratio and Severity of Chronic Coronary Artery Disease

Abstract: Uric acid (UA) to albumin ratio (UAR) is an emerging marker to predict coronary artery disease (CAD)-related events. There is limited data on the relationship between UAR and the severity of the disease in chronic CAD patients. We aimed to evaluate UAR as an indicator for CAD severity using the Syntax score (SS). We retrospectively enrolled 558 patients with stable angina pectoris and underwent coronary angiography (CAG). Patients were divided into 2 groups, according to CAD severity: low SS (≤22) and intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Yalcinkaya et al divided patients with coronary artery disease (CAD) into high and low Syntax score (SS) groups. 1 UAR was significantly higher in the high SS group. They also found that UAR above 1.34 was an independent predictor of high SS with an odds ratio of 3.86 (95% confidence interval: 2.39-6.23 P < .05).…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…Yalcinkaya et al divided patients with coronary artery disease (CAD) into high and low Syntax score (SS) groups. 1 UAR was significantly higher in the high SS group. They also found that UAR above 1.34 was an independent predictor of high SS with an odds ratio of 3.86 (95% confidence interval: 2.39-6.23 P < .05).…”
mentioning
confidence: 74%
“…In summary, the work by Yalcinkaya et al 1 demonstrated that UAR is a useful tool to be used in the risk stratification of CAD. Further studies on the mechanisms of UAR in affecting CAD are warranted.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The findings also revealed a noteworthy correlation between UAR values and the SYNTAX score. Yalcinkaya et al [15] found that UAR levels predict disease burden in participants with chronic CAD and are significantly associated with the SYNTAX and Gensini scores.Çınar et al [34] demonstrated that in patients with STEMI who underwent primary PCI, elevated UAR levels are individual risk factors for the no-reflow phenomenon. Şaylık et al [35] determined that UAR independently predicts poor coronary collateral circulation congestion (CCC) in individuals diagnosed with chronic total occlusion of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%